An evaluation into the potential of biological processing for the removal of metals from sewage sludges - Lombardi, A. T. [UNESP]; Garcia, O. [UNESP] (Crc Press Inc, 1999)
The use of sewage sludge in agricultural land as a means of sludge disposal and recycling has been shown to be economical and suitable because of the presence of nutrients such as nitrogen and phosphorus. However, municipal sludges often contain high quantities of toxic metals and other compounds that must be removed for its safe use in agricultural soils. The biological leaching of metals from sewage sludges has been shown to be a promising technique for metal detoxifying in such complex matrix. The process efficiency is dependent on several physico-chemical parameters, such as total solids concentration, metal forms, pH-ORP, and temperature. Scale-up of the process has not yet been defined and is still pursuing the correct operational design. Current research involving the bioleaching of metals from sewage sludge and its application to land, which affects soil physical properties, are presented and discussed.
Keywords: bioleaching; Thiobacillus; sewage sludge; metals